Adapting Motor Imagery Training Protocols to Surgical Education: A Systematic Review and Meta-Analysis. (June 2021) - Goble, Mary S. L.; Raison, Nicholas; Mekhaimar, Ayah; Dasgupta, Prokar; Ahmed, Kamran
Objective. Motor imagery (MI) is widely used to improve technical skills in sports and has been proven to be effective in neurorehabilitation and surgical education. This review aims to identify the key characteristics of MI protocols for implementation into surgical curricula. Design. This study is a systematic review and meta-analysis. PubMed, MEDLINE, Embase and PsycINFO databases were systematically searched. The primary outcome was the impact of MI training on measured outcomes, and secondary outcomes were study population, MI intervention characteristics, study primary outcome measure and subject rating of MI ability (systematic review registration: PROSPERO CRD42019121895). Results. 456 records were screened, 60 full texts randomising 2251 participants were reviewed and 39 studies were included in meta-analysis. MI was associated with improved outcome in 35/60 studies, and pooled analysis also showed improved outcome on all studies with a standardised mean difference of .39 (95% CI: .12, .67, P = .005). In studies where MI groups showed improved outcomes, the median duration of training was 24 days (mode 42 days), and the median duration of each individual MI session was 30 minutes (range <1 minute-120 minutes). Conclusions. MI training protocols for use in surgical education could have the following characteristics: MI training delivered in parallel to existing surgical training, in a flexible format; inclusion of a brief period of relaxation, followed by several sets of repetitions of MI and a refocusing period. This is a step towards the development of a surgical MI training programme, as a low-cost, low-risk tool to enhance practical skills.